Research on the joining of aluminum alloy and high-strength steel by dieless clinched-adhesive processes - Xiao Ouyang; Chao Chen (Journal of Materials Research and Technology, 2023)
Aluminum and high-strength steel are the best choices for modern cars due to their excellent ratio of strength to weight. As application support, the clinched-adhesive process for aluminum alloys and high-strength steels is also attracting increasingly attention. In this paper, a novel dieless clinched-adhesive process was proposed, which greatly improves the joint strength. It also has unique advantages such as low alignment requirements and low joint bulge due to the use of dieless clinched mould. In the background of automotive light weighting, this joining technology has great prospects for development and application due to its many advantages. Meanwhile, the geometric and mechanical characteristics of various material types of clinched-adhesive joints and clinched joints were analyzed. The key geometric parameters, static strength, and absorbed energy of the joints were obtained. Besides, the microscopic/macroscopic failure mechanisms of joints were investigated. The results showed that the shear strength and energy absorption of the clinched-adhesive joints were much higher than the clinched joints. The highest shear strength of 8159.7 N was obtained for the AL5052-AL5052 material combination, which was 298.3% enhanced compared with the clinched joints. The enhancement of the joint strength was mainly caused by the adhesive. Additionally, the macroscopic failure modes of clinched-adhesive joints and clinched joints with the same material combination are identical, but there are some differences in the microscopic failure mechanisms.